Margaret Chase Smith Library 2015 Student Essay Contest: Reforming the United States Immigration Policy - Kocik, Rachel (Maine Policy Review, 2016)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. In this issue, we feature the three prize-winning essays as the Margaret Chase Smith Essay. The 2015 essay prompt asked students to weigh in with their opinions about what current U.S. immigration policy should be in light of the historical backdrop of alternating cycles of welcome and wariness toward foreigners. Second place prize winner Rachel Kocik discusses some of the many benefits immigrants bring to the United States, while acknowledging that there are still some knotty legal problems that need to be resolved.